Pengaruh penambahan sukrosa pada formulasi sabun padat transparan ekstrak etanol kayu secang - Khoirunnisa, Labbaika; Rianti, Dian Ratna; Azzahra, Fara (Universitas Mataram, 2024)
Transparent solid soap is a soap preparation that had great demand by the public because its attractive. The use of sucrose serves to help the formation of soap transparency. The aimed of this study is to determine the transparacy of sappan wood extract soap by adding different concentration of sucrose. Sappan wood ethanol extracts transparent soap (STEEKS) was made in three concentration of sucrose, FI (10%); FII (15%); and FIII (20%). The soap was tested of organoleptic tests, transparency, pH, foam stability, and soap hardness. The organoleptic test results obtained a transparent solid soap with a red color, strawberry's scent, and a transparent solid texture. The results show, the transparency test of FIII is more transparent than FII and FI (FIII>FII>FI). The pH values for each formula were FI 10.52 ± 0.36; FII 10.44 ± 0.28; FIII 10.35 ± 0.25. The percentage values of foam stability are FI 40.35% ± 6.52; FII 39.50%± 7.91; FIII 39.93% ± 5.19. The hardness value of soap produced in each formula is FI 3.87 Kg ± 0.35; FII 4.60 Kg ± 0.10; FIII 5.13 Kg ± 0.42. The results of the pH and foam stability test did not show significant differences between groups. The hardness of transparent solid soap showed a significant difference between the FI with FII; and FI with FIII groups. According to the study, the sucrose concentration affects soap hardness and transparency.